Controlled Nucleation and Stabilization of Ferroelectric Domain Wall Patterns in Epitaxial (110) Bismuth Ferrite Heterostructures. (16th September 2020) - Zhang, Yangyang; Tan, Yueze; Sando, Daniel; Chen, Long‐Qing; Valanoor, Nagarajan; Zhu, Yimei; Han, Myung‐Geun
Abstract: Ferroelectric domain walls, topological entities separating domains of uniform polarization, are promising candidates as active elements for nanoscale memories. In such applications, controlled nucleation and stabilization of domain walls are critical. Here, using in situ transmission electron microscopy and phase‐field simulations, a controlled nucleation of vertically oriented 109° domain walls in (110)‐oriented BiFeO3 (BFO) thin films is reported. In the switching experiment, reversed domains that are nucleated preferentially at the nanoscale edges of the "crest and sag" pattern‐like electrode under external bias subsequently grow into a stable stripe configuration. In addition, when triangular pockets (with an in‐plane polarization component) are present, these domain walls are pinned to form stable flux‐closure domains. Phase field simulations show that i) field enhancement at the edges of the electrode causes site‐specific domain nucleation, and ii) the local electrostatics at the domain walls drives the formation of flux closure domains, thus stabilizing the striped pattern, irrespective of the initial configuration. The results demonstrate how flux closure pinning can be exploited in conjunction with electrode patterning and substrate orientation to achieve a desired topological defect configuration. These insights constitute critical advancements in exploiting domain walls in next generation ferroelectronic devices. Abstract : The results of in situ TEM investigations of domain switching under applied bias and observation of the fine structure of domain walls down to the atomic scale reveal the dynamic behavior in (110) oriented BiFeO3 thin films. Site‐specific domain nucleation and alternating vertical domain configuration can be achieved by electrode patterning, substrate orientation, and flux‐closure pinning.